Rancang Bangun Aplikasi Berbasis Web Untuk Inventarisasi Benda Seni Budaya Palembang - Shinta Puspasari; Dien Novita; Mgs. Deny Ramadhan (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2015)
This paper describes the design of web-based applications for Palembang inventory of objects of art and culture through digital image documentation. The research methodology includes Rapid Application Development methodology which consists of modelling, implementation, and testing of applications. Inventory of art of cultural objects made through primary and secondary data searches through interviews, observation, and documentation to the Department of Tourism and culture of Palembang City and at the Arts Council of Palembang. The data collection contains 150 intangible cultural objects. The Results of the implementation of application design acquired a site www. PalembangCulture.com which can be accessed by users with different levels of access rights. Applications is expected to facilitate the dissemination of information objects of art and culture that exist and thrive in the city of Palembang and document digital images of objects of art and culture so that they can be accessed globally